Detection of Serum Ferritin in Women with Breast Cancer - Eman S. Nassir (College of Pharmacy University of Baghdad, 2017)
Breast cancer is one of the most common cancers in females. In Iraq there are noticeable elevation in incidence rates and prevalence of advanced stages of breast cancer. Ferritin is intracellular iron storage protein abundant in circulation and its main application in differential diagnosis of anemia. The level of serum ferritin was found raised in various cancers including breast cancer. The aim of this study was to assess whether the serum ferritin concentration would be altered in Iraqi women with breast cancer and it could be related to progression of disease. Sixty eight females participated in this study. The mean age of these females was 53.25Â± 9.52 .The level of serum ferritin was measured in 24 Iraqi women of early stage of breast cancer (stage I and II) and 24 Iraqi women of advanced stage (III and IV). These levels were compared with 20 healthy females as controls. Serum ferritin was estimated by using enzyme linked immune sorbent assay method. This serum ferritin was found to be raised in all breast cancer patients (p<0.05) as compared to controls. The rise in ferritin level was significant in advanced stage (p<0.05) as compared to early stage. Thus the estimation of ferritin may aid in diagnosis, assessment of severity and monitoring of Iraqi women with breast cancer. Key words: - Ferritin, Breast cancer, Iraq.